Proteomic analysis of the regulatory networks of ClpX in a model cyanobacterium Synechocystis sp. PCC 6803 - Zhang, Yumeng; Wang, Yaqi; Wei, Wei; Wang, Min; Jia, Shuzhao; Yang, Mingkun; Ge, Feng (Frontiers in Plant Science, 2022)
Protein homeostasis is tightly regulated by protein quality control systems such as chaperones and proteases. In cyanobacteria, the ClpXP proteolytic complex is regarded as a representative proteolytic system and consists of a hexameric ATPase ClpX and a tetradecameric peptidase ClpP. However, the functions and molecular mechanisms of ClpX in cyanobacteria remain unclear. This study aimed to decipher the unique contributions and regulatory networks of ClpX in the model cyanobacterium Synechocystis sp. PCC 6803 (hereafter Synechocystis). We showed that the interruption of clpX led to slower growth, decreased high light tolerance, and impaired photosynthetic cyclic electron transfer. A quantitative proteomic strategy was employed to globally identify ClpX-regulated proteins in Synechocystis cells. In total, we identified 172 differentially expressed proteins (DEPs) upon the interruption of clpX. Functional analysis revealed that these DEPs are involved in diverse biological processes, including glycolysis, nitrogen assimilation, photosynthetic electron transport, ATP-binding cassette (ABC) transporters, and two-component signal transduction. The expression of 24 DEPs was confirmed by parallel reaction monitoring (PRM) analysis. In particular, many hypothetical or unknown proteins were found to be regulated by ClpX, providing new candidates for future functional studies on ClpX. Together, our study provides a comprehensive ClpX-regulated protein network, and the results serve as an important resource for understanding protein quality control systems in cyanobacteria.